Revščina, ženske in zdravstvena nega - Šmitek, Jana (Obzornik zdravstvene nege, 2005)
Poverty is a constant social phenomenon with a historical background. In the article, the author presents the definition and different forms of poverty anddescribes reasons that prevented efficient abolition of poverty in Eastern European countries, the status of women there and its relation to poverty, as well as the effects of poverty and social exclusion of people because of it. State based interventions are mentioned shortly. Nursing care is closely connected with the problems of poverty. Poverty affects health status. In the frames of nursing care, several actions can be taken to reduce the effects of poverty on health. Even more could have been achieved in cooperation of nursing care with other caring professions in common projects.
Keywords: družbeni položaj; Nursing Care; Poverty; Revščina; woman; Women'S Health; zdravje; Zdravstvena nega; ženske; Ženske, zdravje